A Discrete Bit Loading Algorithm for FBMC/OQAM - Caus, M.; Perez-Neira, A. I.; Garcia-Armada, A. (IEEE signal processing letters, 2012)
In this letter the discrete rate maximization problem is investigated for FBMC/OQAM. The analysis reveals that if there is crosstalk certain bit allocations violate the power constraints. Aiming at ensuring the feasibility along with alleviating the complexity we have devised a novel iterative algorithm, which always converges. Simulation-based results show that the proposed algorithm performs close to the upper bound for high-coherence bandwidth channels. Under highly frequency selective channels the existing algorithms are not able to guarantee the target SER whereas our approach guarantees the QoS.